PERUBAHAN PRESEPSI MASYARAKAT TERHADAP GUS MUDLOR SEBAGAI PEMIMPIN BERBASIS AGAMA DI SIDOARJO - Intan Fadiyah; Agus Mahfud Fauzi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study examines the shifting dynamics of public perception toward Ahmad Muhdlor Ali (Gus Mudlor) as a religion-based leader in Sidoarjo Regency. Initially celebrated as a progressive young leader with strong pesantren credentials, Gus Mudlor gained public legitimacy through his religious background and symbolic identity. However, this perception changed significantly following his involvement in a corruption scandal, which raised questions about the sustainability of religion-based legitimacy in local politics. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation with respondents from two generational groups. The findings reveal that religion provided powerful symbolic capital for electoral success, but legitimacy quickly declined when issues of accountability and governance emerged. Older respondents tended to frame their disappointment through moral-religious narratives, while younger respondents emphasized performance and transparency as the basis for trust. These results highlight that public trust is fluid, continuously negotiated between symbolic identity and practical governance. The study contributes to debates on political legitimacy in Indonesia by showing the conditional nature of religion-based leadership. Limitations include the relatively small number of respondents and the single-case focus. Future research should expand comparative cases and respondent diversity to provide broader insights into the relationship between religion, leadership, and public trust.